2007
DOI: 10.1007/s00198-007-0410-4
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment of osteoporosis: a need for study

Abstract: Summary Adherence to anti-osteoporosis medications is currently low and is associated with poor anti-fracture efficacy. This manuscript reviews the potential design of clinical studies that aim to demonstrate improved adherence, with new chemical entities to be used in the management of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 39 publications
1
61
0
9
Order By: Relevance
“…[55] This assumption is rather conservative since recent data have shown that the treatment benefit achieved (changes in BMD) with 2 years of denosumab therapy was reversed within 2 years of treatment discontinuation. [56] Adherence Adherence to osteoporosis medications is a major concern [57] and may substantially affect costeffectiveness results. [58,59] For modelling purposes, adherence was divided into 'compliance' (i.e.…”
Section: Cost Effectiveness Of Denosumab For Post-menopausal Osteopormentioning
confidence: 99%
“…[55] This assumption is rather conservative since recent data have shown that the treatment benefit achieved (changes in BMD) with 2 years of denosumab therapy was reversed within 2 years of treatment discontinuation. [56] Adherence Adherence to osteoporosis medications is a major concern [57] and may substantially affect costeffectiveness results. [58,59] For modelling purposes, adherence was divided into 'compliance' (i.e.…”
Section: Cost Effectiveness Of Denosumab For Post-menopausal Osteopormentioning
confidence: 99%
“…One of these is that patients affected by osteoporosis and with fragility fractures are not indicated for treatment 5,6 . Another is that once indicated, the patients abandon treatment after a certain period of time, or do not follow the treatment correctly, which is to say that they have poor persistence or adherence [7][8][9][10][11][12][13] , which leads to an increase in the risk of fracture 14,15 . We carried out this study in a population of patients previously diagnosed with osteoporosis and monitored by their primary care doctors, with the aim of understanding some of their clinical characteristics and the possible differences in their adherence to treatment, depending on whether or not they have fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…(8,9) We have previously reported that RIS arrested the tissue aging encountered in untreated osteoporosis, (13) although it should be kept in mind that the study in that report was a clinical trial, thus potentially not representative of the ''real'' world due to likely compliance differences. (30)(31)(32)(33) In addition, differences have been seen in effects on intrinsic bone material properties in animal studies. In a comparative study in normal dogs, 1 year with ALN significantly reduced the work-to-failure/areal BMD relationship in the vertebra compared to placebo, but in animals treated with RIS the relationship was not different from placebo.…”
Section: Discussionmentioning
confidence: 99%